Novel Smartphone Interventions Improve Cognitive Flexibility and Obsessive-Compulsive Disorder Symptoms in Individuals with Contamination Fears. Issue 1 (December 2018) - Jalal, Baland; Brühl, Annette; O'Callaghan, Claire; Piercy, Thomas; Cardinal, Rudolf; Ramachandran, Vilayanur; Sahakian, Barbara
Abstract One type of obsessive–compulsive disorder (OCD) is characterized by contamination fears and compulsive cleansing. Few effective treatments are available for this debilitating condition. Compulsive symptoms, such as excessive washing, are believed to be mediated by cognitive inflexibility—arguably the most striking cognitive impairment in OCD. In this study, we investigated the effects of two novel smartphone interventions on cognitive flexibility and OCD symptoms in healthy individuals with OCD-like contamination fears. In the first intervention, participants watched a brief video recording of themselves engaging in handwashing on a smartphone, four times a day, for a total of one week (N = 31). The second intervention was similar except that participants watched themselves repeatedly touching a disgust-inducing object (N = 31). In a third (control) "intervention", participants watched themselves performing sequential hand movements (N = 31). As hypothesized, the two smartphone interventions, unlike the control, improved cognitive flexibility; as assessed on the Intradimensional–Extradimensional Set Shifting task (a sensitive marker of cognitive flexibility). The two interventions, unlike the control, also improved OCD symptoms (measured with the Obsessive–Compulsive Inventory–Revised and Yale–Brown Obsessive–Compulsive Scale). Finally, we found high levels of adherence to the interventions. These findings have significant clinical implications for OCD.